A Sequential Method for Determining Optimal Stripper Pressure and Terminal Pressure in CO2 Capture and Liquefaction Process Using MEA. Issue 7 (2016) - Park, Taekyoon; Bae, Jaehan; Lee, Chang Jun; Lee, Jong Min
Abstract: The pressure of a distillation column for regenerating an absorbent is one of the key variables for minimizing the energy in a carbon capture and storage (CCS) chain. The steam drag point in power plant, the regeneration energy in capture process and the compression energy in the liquefaction process are highly dependent on the pressure of regeneration column . In this work, a new method for determining optimal value of stripper pressure is proposed based on the integrated simulation model and sequential optimization method. Total required energy has been represented as a function of the stripper pressure and the terminal pressure. The results show that the higher pressure is generally recommended to reduce the required energy, revealing that the value of the stripper pressure depends on the liquefaction process more than the power plant.